Effect of type 3 (oversize) tennis ball on serve performance and upper extremity muscle activity - Blackwell, J.; Knudson, D. (Sports Biomechanics, 2002)
This study investigated the effect of the larger diameter (Type 3) tennis ball on performance and muscle activation in the serve. Sixteen male advanced tennis players performed serves using regular size and Type 3 tennis balls. Ball speed, surface electromyography, and serve accuracy were measured. There were no significant differences in mean initial serve speeds between balls, but accuracy was significantly greater (19.3%) with the Type 3 ball than with the regular ball. A consistent temporal sequence of muscle activation and significant differences in mean activation of different muscles were observed. However, ball type had no effect on mean arm muscle activation. These data, combined with a previous study, suggest that play with the larger ball is not likely to increase the risk of overuse injury, but serving accuracy may increase compared to play with the regular ball.